2021
DOI: 10.1111/cob.12479
|View full text |Cite
|
Sign up to set email alerts
|

Weight bias reduction among first‐year medical students: A quasi‐randomized, controlled trial

Abstract: Summary Implicit and explicit weight bias is prevalent among healthcare professionals and results in negative outcomes, including weak physician‐patient rapport, low patient trust in physicians, and avoidance of healthcare. This study aimed to decrease weight bias in medical students via a one‐session, curriculum‐based intervention founded on the elaboration likelihood model (ELM). First‐year medical students (N = 101) were quasi‐randomly assigned to a group‐based experimental or education‐based control interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 25 publications
(46 reference statements)
1
20
0
Order By: Relevance
“…The first author carefully scanned each title for studies of interest and ultimately reviewed 36 abstracts. Of these 36 articles, 16 were then selected for full article review 9,17,18,33–43 . Two articles 46,47 were removed after a full article review because there was no intervention, leaving 14 articles included in this systematic review.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The first author carefully scanned each title for studies of interest and ultimately reviewed 36 abstracts. Of these 36 articles, 16 were then selected for full article review 9,17,18,33–43 . Two articles 46,47 were removed after a full article review because there was no intervention, leaving 14 articles included in this systematic review.…”
Section: Resultsmentioning
confidence: 99%
“…Methodological characteristics are represented in Table 2. Most studies ( n = 11) 9,17,18,34–37,39,40,41,42 used a pre‐test, post‐test quasi‐experimental design, with five studies including additional data collection time points at 1 month, 17,40,43 4 months 37 and yearly for 4 years 36 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 144 ] Personal biases, both explicit and implicit, have been noted in physicians which can affect the delivery of care. [ 145 146 ] Physicians have reported that their busy schedules may not allow enough time to spend on the care of obesity. [ 147 ] Primary and secondary care facilities may not have dieticians, educators and psychologists with expertise regarding management of obesity.…”
Section: B Arriers To O Besity ...mentioning
confidence: 99%